Challenges in the studies of comparative constructions of gender equality - Rönnblom, Malin (The Greek Review of Social Research, 2016)
Why are comparisons interesting, or what are comparisons all about? In this article, the comparative ambition in the social constructivist tradition is scrutinized, and the other articles of the issue are used as examples of what is seen as principle problems of comparative studies. The first part of the article deals with the need of reflexivity in order for the researcher to avoid implicit notions of «good gender equality» or «real feminism». In the second part, the problems of comparative studies are more specifically addressed, by both discussing the traditional legacy of comparative politics and bringing forward possible alternatives for non-positivistic comparative analyses. The article ends by asking for a reflexive intersectional comparative approach.